The total solute-water correlation function for Lennard-Jones particles - Smith, Ana-Suncana; et al. (Fizika A (Zagreb), 2005)
A series of molecular dynamic simulations have been performed in order to evaluate the Lennard-Jones particle-water correlation function for solutes ranging in size from 0.3 to 1.2 nm. The results of these simulations have provided evidence for distinct orientational ordering of water molecules with respect to the solute. Furthermore, this orientational ordering is determined to be longer in range than the well-known radial ordering. Although the distance from the solute at which the correlation with water can be detected is independent of the size of the solute, the amplitude of the correlation function is sensitive to the size in the first hydration shell.
Keywords: solute-water correlation function; molecular dynamic simulations; Lennard-Jones particle